Assessing staining resistance of a CAD/CAM interpenetrating network composite material - Mehmet Mustafa Özarslan; Ulviye Şebnem Büyükkaplan; Çağatay Barutcigil; Merve Özarslan; Kubilay Barutcigil; Nurullah Türker (Head & Face Medicine, 2018)
Abstract Background Color change of dental materials over time because of staining agents has important effects on the long-term prognosis of dental esthetic treatments. In the present study, staining resistance of an interpenetrating network composite material with different translucency levels (translucent and high translucent) and various surface procedures for finishing were investigated. Methods Same shade CAD/CAM interpenetrating network composite specimens having two different translucency levels were prepared using by a water cooling cutting saw. Specimens were grouped and different finishing procedures were performed. Then, specimens were kept in distilled water, red wine and coffee for different periods. Color was evaluated before and after exposure to staining liquids using a clinical spectrophotometer. Results In the 7 days Glaze group (ΔE00 > 2.2), color difference was only perceivable in the specimens kept in red wine. In the 28 days red wine high translucent groups, only the high translucent Clinical group showed a clinically acceptable (ΔE00 < 2.2) color change. In the translucent groups kept in red wine, only the translucent Glaze group showed a clinically perceivable color change (ΔE00 > 2.2). In the 28 day measurements, all the translucent groups showed a clinically perceivable color change (ΔE00 > 2.2). Of the translucent groups kept in coffee for 28 days, it was observed that only the translucent Clinical group demonstrated a clinically non-perceivable color change (ΔE00 < 2.2). Conclusions All the translucent groups kept in red wine showed a clinically perceivable color change after 28 days. Only the high translucent Clinical Kit group showed a clinically acceptable color change. Among high translucent and translucent specimens kept in coffee only the translucent Clinical group showed a clinically acceptable color change after 28 days.